Applying Attributes of Contemplative Technopedagogy to a Social Media Assignment - Shanks, Justin D.; Young, Scott W. H. (Frontiers in Education, 2019)
With widespread prevalence of digital technology in contemporary higher education, researchers have been keen to identify best practices and understand impacts. Social media present opportunities to cultivate interactive, creative teaching-learning communities. However, inclusion of social media in a course does not necessarily equal deep or creative student engagement. Faculty play an important role in helping students critically and creatively engage with content, colleagues, and context. Utilizing a mixed-methods case study approach, this research explores how contemplative technopedagogy can aid in the development of social media assignments and positively influence student learning. While blogging has been studied as a pedagogical tool, Tumblr has not yet been studied as an educational technology. This research demonstrates how the integration of contemplative technopedagogical attributes can aid faculty in developing social media assignments with contextual awareness that enhance teaching and learning in contemporary higher education.